Do Differences in Livestock Management Practices Influence Environmental Impacts? - Kleppel, Gary S. (Frontiers in Sustainable Food Systems, 2020)
Herbivore-carnivore interactions are fundamental to grassland ecosystem functionality and to the human cultures that have long depended on these ecosystems for their nutrition. However, a large literature has developed during the past century indicating that animal agriculture is responsible for numerous negative environmental impacts. In this paper, I review literature on some of the environmental impacts of two different livestock management approaches, industrial-conventional (IC) management and regenerative-multi-paddock (RM) management. I consider the null hypothesis that the environmental impacts of ruminant livestock production are independent of the approach used to manage animals and grazing lands. It evident in the literature that managed grazing ecosystems are complex, and for certain system attributes, such as forage quality and plant community structure, the better management system is difficult to discern. In other areas definitive differences in impacts appear clearly management dependent. For instance, the soils of RM grasslands exhibit higher microbial biomass and diversity, and higher fungal: bacterial ratios than IC soils. Several impacts associated with livestock production appear to have less to do with grazing, per se, and more to do with support factors, such as feed production and manure management. The compilation of data from numerous sources suggests that RM management may reduce blue withdrawals and GHG emissions by >50%, relative to IC management. Accumulating data also suggest that a significant portion of anthropogenic CO2-eq emissions can be removed from the atmosphere and stored in the soil by applying RM management practices. Finally, it is suggested that while research design may affect the outcomes of some studies, the quality and quantity of the science may not resolve many discrepancies in the data. It is suggested that the viability and sustainability of animal agriculture may depend upon broadening the goals of practitioners to include both food production and the restoration and protection of agricultural ecosystem services.